Plasma Biomarker for Post-concussive Syndrome: A Pilot Study Using an Alternating Current Electro-Kinetic Platform - Lewis, Jean M.; Dhawan, Sanjay; Obirieze, Augustine C.; Sarno, Benjamin; Akers, Johnny; Heller, Michael J.; Chen, Clark C. (Frontiers in Neurology, 2020)
Background: Technology platforms that afford biomarker discovery in patients suffering from traumatic brain injury (TBI) remain an unmet medical need. Here, we describe an observational pilot study to explore the utility of an alternating current electrokinetic (ACE) microchip device in this context. Methods: Blood samples were collected from participating subjects with and without minor TBI. Plasma levels of glial fibrillary acidic protein (GFAP), Tau, ubiquitin C-terminal hydrolase L1 (UCH-L1), and cell-free DNA (cfDNA) were determined in subjects with and without minor TBI using ACE microchip device followed by on-chip immunofluorescent analysis. Post-concussive symptoms were assessed using the Rivermead Post Concussion Symptoms Questionnaire (RPCSQ) at one-month follow-up. Results: Highest levels of GFAP, UCH-L1, and Tau were seen in two minor TBI subjects with abnormality on head computed tomography (CT). In patients without abnormal head CT, Tau and GFAP levels discriminated between plasma from minor-TBI and non-TBI patients, with sensitivity and specificity of 64-72% and 50%, respectively. Plasma GFAP, UCH-L1, and Tau strongly correlated with the cumulative RPCSQ score. Plasma UCH-L1 and GFAP exhibited highest correlation to sensitivity to noise and light (r=0.96 and 0.91, respectively, p<0.001). Plasma UCH-L1 and Tau showed highest correlation with headache (r=0.74 and 0.78, respectively, p<0.001), sleep disturbance (r=0.69 and 0.84, respectively, p<0.001), and cognitive symptoms, including forgetfulness (r=0.76 and 0.74, respectively, p<0.001), poor concentration (r=0.68 and 0.76, respectively, p<0.001), and time required for information processing (r=0.77 and 0.81, respectively, p<0.001). cfDNA exhibited a strong correlation with depression (r=0.79, p<0.01) and dizziness (r=0.69, p<0.01). While cfDNA demonstrated positive correlation with dizziness and depression (r=0.69 and 0.79, respectively, p<0.001), no significant correlation was observed between cumulative RPCSQ and cfDNA (r=0.07, p=0.81). Conclusion: We provide proof-of-principle results supporting the utility of ACE microchip for plasma biomarker analysis in patients with minor TBI.